Strategi Pemasaran pada Masa Pandemi dalam Upaya Meningkatkan Tingkat Hunian Kamar Hotel di Jember (Studi Kasus di Hotel Bintang Mulia) - Hadi Jatmiko; Cristian Rizqi Anggraini (STIEPAR YAPARI Bandung, 2022)
This study aims to analyze the right marketing strategy to increase the room occupancy rate during the pandemic. The population of this study were employees at the Bintang Mulia hotel with a proportional random sampling of 44 respondents. Structured interviews with hotel managers and associations. The research analysis method uses SWOT analysis. The results of the study stated that the position of the Bintang Mulia hotel was in Quadrant I, this was based on the results of the IFAS and EFAS analysis. The strategy that can be applied is an aggressive growth policy (growth-oriented strategy, while alternative strategies include: First, implementing an online booking system which is expected to provide convenience for guests. Second, getting used to the application of health protocols that guests are expected to feel safe. Third, maintaining and improve the quality of its services, improvement efforts can be made through assessments from visitors through feedback in the form of ratings and reviews on travel agent applications. Fourth, collaborate with genpi, influencers, and the government.